Lignin structure defines the properties of asphalt binder as a modifier. (6th December 2021) - Zhang, Ran; Sun, Su; Wang, Lei; Guo, Li; Shi, Qipeng; Jia, Jia; Zhang, Xiaoyu; Yu, Hongbo; Xie, Shangxian
Graphical abstract: Lignin, a sustainable superior asphalt binder modifier, regulates the performance of asphalt binder by variable structure and functional groups. Highlights: Soda lignin was excellent asphalt modifier to improve the low-temperature property. Soda lignin with dominant β- O -4′ formed stronger multiple intermolecular H-bonds. Stronger multiple intermolecular H-bonds favored the low-temperature property. Kraft lignin with dominant C–C formed stronger dimeric intermolecular H-bonds. Stronger dimeric intermolecular H-bonds explained the high-temperature property. Abstract: This study aims to further illustrate the relationship between technical lignin structure and asphalt binder performance. Two types of technical lignins (soda lignin and kraft lignins), were prepared and fully characterized. Rheological performance tests were performed to study their effects on the asphalt binder performance. Soda lignin was dominated by linear β- O -4′ aryl ethers and possessed more multiple intermolecular H-bonds, which effectively enhanced the low-temperature performance by weakening the cross-linking between asphaltenes and lignins. Kraft lignin, which exhibited condensed C–C linkages and stronger dimeric intermolecular H-bonds, performed as an effective asphalt binder modifier to improve the high-temperature rutting resistance.